A Comparative Study of Heavy Metals and Trace Elements Concentration in Milk Samples Consumed in Iraq - Nada M. Hasan (مجلة بغداد للعلوم, 2020)
The measurements of major and trace elements in different brands of milk powder selected from the Iraqis market via the X-ray fluorescence (XRF) Technique have been studied in the present work. The result of the measurements reveals the high concentrations of sodium, phosphorus, sulfur, chlorine, potassium, calcium and magnesium. Furthermore, low concentrations of aluminum, silicon, iron, bromine, molybdenum, iodine, barium, titanium, manganese, cobalt, chrome, nickel, copper, zinc and lead were detected. Neutron activation analysis (NAA) and Kjeldahl technique were also employed to determine the concentrations of nitrogen. It was found that the nitrogen concentration was in the range of (1.96 - 3.23) % which is within the permissible limits. The concentrations of the trace elements (copper, manganese, zinc, lead) were verified via the atomic absorption spectrometer (AAS) technique. The results are compared with the authorized limit by the food and agriculture organization and the world health organization (FAO/WHO) standards.